2020
DOI: 10.3367/ufne.2018.04.038417
|View full text |Cite
|
Sign up to set email alerts
|

Complex phase diagrams of systems with isotropic potentials: results of computer simulations

Abstract: This review is based on a talk by the authors at the field Scientific session of the Physical Sciences Division of the Russian Academy of Sciences devoted to the 60th anniversary of the Vereshchagin Institute for High Pressure Physics of the Russian Academy of Sciences. The dependence of phase-diagram characteristics and phase transitions on the shape of the intermolecular potential is reviewed and analyzed for two- and three-dimensional systems with isotropic interaction. First, the case of monotonic repulsiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 260 publications
0
20
0
Order By: Relevance
“…It has long been known that water-like anomalies also appear in particles interacting with isotropic potentials that have two lengthscales, comprising a short-range hard-core repulsion and an intermediate range soft-core repulsion [149][150][151][152]. In these models two typical interparticle distances compete at different thermodynamic conditions.…”
Section: Alternative Modelsmentioning
confidence: 99%
“…It has long been known that water-like anomalies also appear in particles interacting with isotropic potentials that have two lengthscales, comprising a short-range hard-core repulsion and an intermediate range soft-core repulsion [149][150][151][152]. In these models two typical interparticle distances compete at different thermodynamic conditions.…”
Section: Alternative Modelsmentioning
confidence: 99%
“…While in a 3D space melting always occurs through a first-order phase transition, in 2D crystals there are known at least three different melting scenarios. To date, for microscopic description of 2D melting there are three recognized scenarios [1,2]: (i) the theory of Berezinskii -Kosterlitz -Thouless -Halperin -Nelson -Young (BKTHNY), according to which melting occurs via two continuous transitions with an intermediary hexatic phase with quasi-long-range orientational order and short-range translational order [3][4][5][6][7]; (ii) melting in one transition of the first order [8,9]; (iii) the crystal-hexatic phase transition takes place by means of a continuous transition of the Berezinskii -Kosterlitz -Thouless (BKT) type, whereas the hexatic phase-isotropic liquid transition -through a first-order transition [10][11][12][13][14]. This makes 2D systems extremely complex and interesting to study.…”
Section: Introductionmentioning
confidence: 99%
“…The phase diagrams of RSS in 2d [32][33][34][35][36][37][38], 3d [31,[39][40][41][42] and very strong confinement (only one layer of the particles in a slit pore) [43] are reported in our recent papers. It was shown that this system demonstrate very complex phase behavior.…”
Section: Introductionmentioning
confidence: 99%